Rancang Bangun Kontrol Pemadaman Listrik Rumah Via SMS Dengan Lampu Emergency Inverter - Yanuar Gustiyandi; Indah Sulistiyowati (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2018)
Electricity is the main source of energy that humans need for everyday life, without electricity a human can not turn on the television, the fridge, and which is sure to be dark because it can not turn on the lights at night. Therefore electricity is very important and can be a major requirement in this life, recently there are frequent blackouts in turn by PLN. The problem is that during the night there is a blackout the house will be dark because the lights will also die, and that's when it takes a tool to turn on the house lights to be able to illuminate the house when there is a power outage. The tool is an inverter run by batteries with 12 volt DC voltage that replaces 220 volt voltage from PLN and also can control via SMS if at any time of power outage. The inverter circuit will be active when there is a power outage and the arduino as a microcontroller triggers the SIM 900 sms module to send a message to the homeowner to confirm the inverter is activated or not, if the inverter is active then the lamp will turn on and if the inverter is off then the lamp will stay off. So that will be generated appliance control of house electricity blackout by sms with emergency lamp run by DC to AC inverter.